Molecular Detection of Torque Teno Sus Virus and Coinfection with African Swine Fever Virus in Blood Samples of Pigs from Some Slaughterhouses in Nigeria. (19th October 2016) - Luka, Pam D.; Erume, Joseph; Yakubu, Bitrus; Owolodun, Olajide A.; Shamaki, David; Mwiine, Frank N.
Abstract : Torque teno sus virus 1 (TTSuV1a/TTSuV1b) infection is present in pig herds worldwide. This study investigated the prevalence of TTSuV1a/TTSuV1b infections in domestic pigs from some slaughterhouses in Nigeria as well as coinfection with African swine fever virus (ASFV) and described the phylogeny in relation to global strains. One hundred and eighty-one (181) blood samples from four slaughterhouses were used for the study and viral nucleic acid detection was carried out by PCR. Comparative sequence analysis was carried out to infer phylogeny. The overall prevalence of TTSuV1a/b was 17.7%. Prevalence of individual genotypes was 10.5% and 7.2% for TTSuV1a and TTSuV1b, respectively. Coinfection of ASFV/TTSuV1a/b was 7.7% while that of TTSuV1a and TTSuV1b was 1.7%. ASFV alone was detected in 11.91% of the total samples. The Nigerian TTSuV1a and TTSuV1b shared a sequence identity of 91–100% and 95–100%, respectively, among each other. The ASFV sequences were 100% identical to members of genotype 1. This is the first report on the presence of TTSuV1a/b in domestic pigs in Nigeria and coinfection with ASFV. Although the prevalence of TTSuV1a/b in Nigeria was low, we recommend further studies to establish the trend and possible role in the pathogenesis of ASFV.